Thermal oxidation and heterogeneous combustion of AlH3 and Al: A comparative study. (February 2021) - Liu, Jianzhong; Yuan, Jifei; Li, Heping; Pang, Aimin; Xu, Peihui; Tang, Gen; Xu, Xingxing
Abstract: Aluminum hydride (AlH3 ) is currently receiving considerable attention due to its potential to replace aluminum (Al) as a new metal fuel in solid propellants. In this study, simultaneous thermogravimetric analysis and differential scanning calorimetry and a laser ignition testing system were used to investigate the thermal oxidation and combustion characteristics of AlH3 and Al. The combustion residues were then analyzed using a scanning electron microscope. Results show that the thermal oxidation processes of both AlH3 and Al contain a mass loss stage and two mass gain stages. After dehydrogenation, AlH3 exhibits a stepwise oxidation behavior that is similar to that of a similar sized Al, but has a much higher mass gain. The combustion process of Al can be divided into three stages, which correspond to the combustion of dispersed Al particles, formation of Al agglomerate and combustion of Al agglomerate, respectively. The combustion flame of AlH3 is significantly different from that of Al, but their microscopic combustion behaviors are very similar. A unique flame delamination phenomenon exists in the early stage of AlH3 flame development. AlH3 has shorter ignition delay times and a larger combustion intensity than Al. The release and combustion of hydrogen changes the combustion environment of the remaining AlH3 particles, leading to the appearance of an OH characteristic peak and increasing the production path of AlO. The morphology of combustion residues shows that the dehydrogenation of AlH3 starts from the particle surface and then gradually expands towards its interior. Highlights: TG-DSC was used to contrastively study thermal oxidation properties of AlH3 and Al. Combustion flames, micro-combustion behaviors and emission spectra were analyzed. Hydrogen plays a critical role in the combustion of AlH3 . Dehydrogenation/passivation mechanism of AlH3 was analyzed.